Adaptive tracking controller design for double-pendulum tower cranes. (November 2020) - Ouyang, Huimin; Tian, Zheng; Yu, Lili; Zhang, Guangming
Abstract: In practical application, the payload swing of tower crane often presents double-pendulum characteristics, which makes it difficult to obtain good performance by existing control methods. Because of this, so far, there are few literatures about the anti-swing and positioning control of double-pendulum tower cranes. At the same time, when the system model parameters are uncertain and there exist external disturbances, the design of the controller becomes more difficult. Therefore, a nonlinear adaptive tracking controller is designed to solve the above problems without a linearized crane model. The stability of this closed-loop control system is theoretically proved by the Lyapunov technique and LaSalle's invariance theorem. After a large number of simulations, the proposed controller not only achieves good positioning and anti-swing performance, but also exhibits strong robustness to model parameter uncertainties and external disturbances.